2001
DOI: 10.1084/jem.193.5.621
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Hematopoietic/Mesenchymal Interaction during Initiation of Peyer's Patch Organogenesis

Abstract: Mice deficient in lymphotoxin β receptor (LTβR) or interleukin 7 receptor α (IL-7Rα) lack Peyer's patches (PPs). Deficiency in CXC chemokine receptor 5 (CXCR5) also severely affects the development of PPs. A molecular network involving these three signaling pathways has been implicated in PP organogenesis, but it remains unclear how they are connected during this process. We have shown that PP organogenesis is initiated at sites containing IL-7Rα+ lymphoid cells and vascular cell adhesion molecule (VCAM)-1/int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
228
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(236 citation statements)
references
References 40 publications
7
228
1
Order By: Relevance
“…The fetal intestinal stromal cells that are engaged by lymphoid tissue inducer cells during the earliest stages of PP development express the VCAM-1 and ICAM-1 adhesion molecules (20). Stimulation of the LT␤R on the stromal cells by membrane bound LT␣ 1 ␤ 2 on the inducer cells is a pivotal initial signal driving organogenesis of PP and lymph nodes (20). LT␣ expression by hemopoietic cells and LT␤R expression by stromal cells are also required for the development of ILF (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fetal intestinal stromal cells that are engaged by lymphoid tissue inducer cells during the earliest stages of PP development express the VCAM-1 and ICAM-1 adhesion molecules (20). Stimulation of the LT␤R on the stromal cells by membrane bound LT␣ 1 ␤ 2 on the inducer cells is a pivotal initial signal driving organogenesis of PP and lymph nodes (20). LT␣ expression by hemopoietic cells and LT␤R expression by stromal cells are also required for the development of ILF (14).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoid tissue inducer cells are CD3 Ϫ CD4 ϩ CD45 ϩ cells that also express the t isoform of the ROR␥ transcription factor (24,25). The fetal intestinal stromal cells that are engaged by lymphoid tissue inducer cells during the earliest stages of PP development express the VCAM-1 and ICAM-1 adhesion molecules (20). Stimulation of the LT␤R on the stromal cells by membrane bound LT␣ 1 ␤ 2 on the inducer cells is a pivotal initial signal driving organogenesis of PP and lymph nodes (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been implicated in lymphocyte recruitment from the bloodstream [2][3][4], the structural compartmentalization of T-B microdomains [5][6][7] and T-B cell interactions within the tissue [8]. Recent studies have demonstrated that the same chemokines (CK) are required for the embryonic development and organization of the majority of secondary lymphoid organs [9], being produced by a subset of mesenchymal cells (VCAM-1 + LTbR + , "organizers") in the early lymphoid anlagen [10,11]. It has been suggested that these CK contribute to the clustering of the earliest wave of hematopoietic cells (CD3 -CD4 + LTb + , "inducers"), preceding peripheral node addressin (PNAd) + high endothelial venule (HEV) formation, T-B lymphocyte compartmentalization and follicular dendritic cell (FDC) network development [12].…”
Section: Introductionmentioning
confidence: 99%
“…progenitors and pro-T cells in adult animals (26), and stimulation of IL-7Ra induces expression of LTa 1 b 2 in IL-7Ra + c-Kit + progenitors (42). In this study, the generation and macroscopic analysis of IL-7Ra-cre;LTb F/F mice found them to phenocopy Krt-5-cre;LTb F/F mice (Fig.…”
Section: Lymph Node Aplasia In Germline Ltb-deficient Mice Does Not Imentioning
confidence: 91%